7 - Médias, pluralisme et organes de régulation en Afrique de l’Ouest - Moustapha Samb (Africa Media Review, 2008)
The crisis resulting from the State monopoly over communications infrastructure and its corollary, the advent of multiparty democracy, called for the creation of regulatory bodies in many West African countries. As a result, the distribution of the audiovisual landscape among the various protagonists and its management have become problematic. In other words, it is a question of how the regulatory bodies will be able to guarantee equitable access to State media for all political parties, including the other attendant forces and, more importantly, better manage the liberalisation of the new audiovisual space in Africa?